АДМІНІСТРАТИВНИЙ ДОГОВІР ЯК ФОРМА РЕГУЛЮВАННЯ АДМІНІСТРАТИВНИХ ВІДНОСИН - Бандурка, Олександр Олександрович (SUPREMANCE OF LAW, 2017)
In the article the analysis of scientific views concerning the problem of definition of the administrative contract in administrative law of Ukraine. According to the results of the study and system analysis identified the major signs of the administrative contract and possible ways of solving the problems of such a definition.
Keywords: administrative contract; the will of the parties; the subject of powers; the public contract